Prolapsus Uteri pada Pasien Berusia 53 Tahun Multipara : Sebuah Laporan Kasus - Syarina Syafira; Iskandar Albin (STIKES Columbia Asia Medan, 2024)
Pelvic organ prolapse is a disease that combines a group of disorders of the ligamentous apparatus of the uterus and vagina, leading to prolapse and prolapse of the internal genital organs, manifested by displacement of the genitals to the vaginal inlet or prolapse beyond its redistribution. A case has been reported from a female patient aged 53 years with complaints of lumps coming out of the vagina. The complaint begins with discomfort and feels like there is a burden on the pelvis. The complaints felt by the patient were aggravated when squatting and lifting heavy objects that made the lump come out of the vagina, the lump decreased when sitting and lying down. On physical examination, it was found that the uterine mass came out of the vaginal introitus in a round shape of pink, the distal part of the uterine prolapse decreased by 1.6 cm from the hymen and no more than TVL (Total Vaginal Length) by 2 cm. Management in patients with operative measures is the laparotomy with total hysterectomy.